Geochronopolitical Identity of Capitals of a Problematic Statehood: Research Question - I. Yu. Okunev (Сравнительная политика, 2015)
The article describes the methodological basis of the study of the spatial identity of the fake capital cities held a Сlub of Geopolitical Studies at MGIMO